Neonatal E. coli infection alters glial, cytokine, and neuronal gene expression in response to acute amphetamine in adolescent rats - Bland, Sondra T. (2010)
Neonatal bacterial infection in rats alters the responses to a variety of subsequent challenges later in life. Here we explored the effects of neonatal bacterial infection on a subsequent drug challenge during adolescence, using administration of the psychostimulant amphetamine. Male rat pups were injected on postnatal day 4 (P4) with live Escherichia coli (E. coli) or PBS vehicle, and then received amphetamine (15 mg/kg) or saline on P40. Quantitative RT-PCR was performed on micropunches taken from medial prefrontal cortex, nucleus accumbens, and the CA1 subfield of the hippocampus. mRNA for glial and neuronal activation markers as well as pro-inflammatory and anti-inflammatory cytokines were assessed. Amphetamine produced brain region specific increases in many of these genes in PBS controls, while these effects were blunted or absent in neonatal E. coli treated rats. In contrast to the potentiating effect of neonatal E. coli on glial and cytokine responses to an immune challenge previously observed, neonatal E. coli infection attenuates glial and cytokine responses to an amphetamine challenge.